Dampak Psikologi dan Etika Profesi Tenaga Kesehatan Terkait Pengesahan UU Kesehatan No.17 Tahun 2023 di Rumah Sakit Undata Sulawesi Tengah - Muh. Ardi Munir; Elli Yane Bangkele; Rahma Dwi Larasati; Amirah Basry (Jurnal Ners, 2025)
Ratification of Health Law no. 17 of 2023 is considered not to reflect meaningful community participation, thus potentially giving rise to legal uncertainty for professional organizations, including medicine, dentistry, nursing, midwifery and pharmacy. This caused controversy and became a concern for many groups in Indonesia. Especially those related to the subject of supervision itself, namely medical personnel and health workers. The aim of the research is to identify a picture of the psychological impact and professional ethics of health workers from the ratification of Health Law No. 17 of 2023 at Undata Hospital, Central Sulawesi. This research is a descriptive analytical research with a cross sectional research design. The samples in this study were health workers who met the inclusion criteria, namely 65 people. Data analysis using the SPSS program. The research results showed that 58 health workers showed good psychology (89.2%) and 7 health workers who showed poor psychology (10.8%). Meanwhile, there were 51 health workers who showed good professional ethics (78.5%) and 14 health workers who showed poor professional ethics (21.5%). The conclusion of this research is that the ratification of Health Law No. 17 of 2023 has had a psychological impact and the impact of good professional ethics on health workers at Unndata Regional Hospital, Palu.